Kompetensi pembangunan sumberdaya manusia dan pemindahan teknologi dan kaitannya dengan prestasi kerja agen pendidikan pengembangan - Rahim M. Sail (Universiti Kebangsaan Malaysia, 2010)
This study was based on the iceberg model of Spencer and Spencer (1993) to show that only “visible” or “surface” competencies are used to measure extension agents’ competency and job performance. The competencies are human resource development (HRD) and transfer of technology (ToT) competencies. Through the survey method questionnaires were distributed 79 extension agents of an extension agency in Selangor. The survey was conducted in September 2008. The questionnaire was developed by the researcher using three components of the HRD competency and three components of ToT competency. The results of the study showed that job performance of the respondents as well as their HRD and ToT competencies were low to medium levels. However, the respondents indicated that the HRD and ToT competencies were important in their jobs to empower clients. Dissemination of agricultural technology information and decision-making competencies explained the 84.3 percent of the variance in job performance of extension agents, It is recommended that extension agents be equipped with knowledge and skills in HRD and ToT through regular training programmes so that they can effectively function at their jobs